Kauçuk Gövdeli Motor Takozunun Sonlu Elemanlar Yöntemiyle Modelleme, Simülasyon Ve Testleri - Coşkun, Görkem (Fen Bilimleri Enstitüsü, 2010)
Kauçuk konstrüksüyon geliştirmede en büyük problem, kauçuğun doğrusal olmayan, zamana ve yük tekrar sayısına, pişme yöntem ve değişkenlerine bağlı mekanik özelliklerine ampirik ve analitik olarak hakim olmanın güçlüğüdür, özellikle de ortada kesinleşmiş bir konstrüksüyon yokken. Bu çalışmada bitmiş konstrüksüyona ihtiyaç duyulmaksızın, sabit kalınlıktaki arıplakalardan standart ölçülerde kesilmiş denekler üzerinde yapılan mekanik test sonuçlarının, sonlu elemanlar yazılımına girilmesi, ve yazılımda bir defa doğru malzeme modeli elde edildikten sonra, bu malzemenin atandığı karmaşık konstrüksüyonların çeşitlilik arz eden testlerinde dahi, sanal ortamda tasarlananla, bu doğrultuda imal edilen bitmiş parçanın test sonuçlarının çakışacağını göstermektir. Böylelikle , istenen mekanik davranış çerçevesindeki nihai konstrüksüyon yazılım üzerinde oluşturulup, bitmiş parça için prototip kalıp bir defa üretilmiş olur

The most difficult problem in developping a rubber construction is the difficulty of amprical and analytic control over the non-linear and time dependent mechanical behaviour of the rubber being highely effected by the number of repetitive loading cycles , as well as by the type and parameters of curing. Particularly if there isn’t any certain completed construction in use. In this work , it’s aimed to show , that final-construction-independant rubber material properties for an FEA software can be obtained , using the experimental resulsts of simple lab-slabs only. And once the appropriate material model is acquired, it’s quite possible to obtain succesfully coinciding load-displacement curves for the final shape of the real part and its corresponding FEM model , even for different sorts of mechanical tests of varying complexity. Hence the final construction shape of the part can be completed thoroughly on a software platform, within any mechanical limitations requested by the client, asiding the necessity of manifacturing several moulds for provisional trial constructions before reaching the appropriate final one.
Fea And Experimental Results Of A Rubber Engine Support
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2004
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2004
Keywords: Olmayan Elastisite; Histerisis; Vizkoelastiklik; Rijitlik Kaybı; Pişme Koşull; Non-linear Elasticity; Hysterisis; Viscoelasticity; Loss of Stiffness; Curing Parameters.